Violence and Gangs: Gender Differences in Perceptions and Behavior - Deschenes, Elizabeth Piper (Journal of quantitative criminology, 1999)
Most research on violence has focused on males, but recent studies indicatethat females are also involved in violent crimes. Few studies, to date,have examined whether different or similar models explain male and femaleinvolvement in violent behavior. In the current research, we examine therelative contribution of social bond, self-control and social learningconcepts to the explanation of male and female violent offending. We alsoexplore the unique contribution of gang membership, school environment andprior victimization to these explanatory models. Using a multisite sampleof eighth-grade students, we find that results of a Chow test indicate theneed for separate theoretical models. Despite some similarities, differentfactors account for male and female rates of violent behavior.